Upscaling Participatory Action and Videos for Agriculture and Nutrition (UPAVAN) trial in rural Odisha, India: Impact, process and economic evaluation results and lessons learnt (Webinar session 2) - Upscaling Participatory Action and Videos for Agriculture and Nutrition; Varrat, Ekjut (International Maize and Wheat Improvement Center, 2023)
The TAFSSA CGIAR Initiative is hosting a series of webinars to highlight research from South Asia on food security, sustainable healthy diets, farmer livelihoods and resilience, and land, air, and groundwater conservation. For the second webinar on January 25, the UPAVAN team presented results from the trial in Odisha, India. Maternal and child undernutrition have adverse consequences for pregnancy outcomes and child morbidity and mortality, and they are associated with low educational attainment, economic productivity as an adult, and human wellbeing. ‘Nutrition-sensitive’ agriculture programs could tackle the underlying causes of undernutrition. The UPAVAN trial has built critical evidence around strengthening agriculture for improved nutrition outcomes. The presenting UPAVAN team included LSHTM (lead); Institute for Global Health, UCL; Digital Green, D-COR; VARRAT, Ekjut; and John Snow Research and Training Institute.